(untitled) (Indian Journal of Animal Production and Management, 2024)
Eighteen Hampshire sows with their litters were randomly selected and divided into three groups keeping similar parities and equal average body weight of dams and their piglets in each group from 4th week onwards such as unrestricted suckling (T1), 6 hours restricted suckling (T2) and 12 hours restricted suckling (T3) groups.All the animals were reared under standard feeding and management conditions. Weaning of piglets was done at 8th week of age. The average body weight of piglets at 8th week was 9.66±0.39, 10.48±0.19 and 12.00±0.22 kg in T1, T2 and T3 groups, respectively. The average daily body weight gain of piglets from 4th to 8th week of age was 0.139±0.01, 0.164±0.01 and 0.220±0.01 kg in T1, T2 and T3 groups, respectively. There was highly significant difference (P<0.01) among the suckling groups in respect of both body weight and daily body weight gain from 5th week onward. The average body weight and daily body weight gain of piglets in T3 group were significantly highest. The average body length was 46.16±0.75, 51.37±0.41 and 53.84±0.52 cm; heart girth was 46.96±0.82, 51.28±0.42 and 50.74±0.40 cm and height at wither was 31.82±0.30, 33.93±0.28 and 38.20±1.29 cm in T1, T2 and T3 groups, respectively at 8th week of age. Highly significant difference (P<0.01) of the body measurements was observed among the suckling groups from 5th week onward. All the body measurements were lower (P<0.05) in T1 group than the T2 and T3 groups. The overall correlation coefficient of body weight with body length (0.87), heart girth (0.88) and height at wither (0.67) was highly significant (P<0.01). The regression coefficient of body weight on body length and heart girth was also highly significant (P<0.01), but regression coefficient of body weight on height at wither was non-significant. There was difference (P<0.05) of average daily feed consumption among the suckling groups. The average daily feed consumption was higher (P<0.05) in T3 group (0.176±0.01 kg ) than that of T1 (0.139±0.01kg) but it did not differ significantly from T2 (0.162±0.01kg). The average cost of feeding per kg body weight gain in piglets were worked out to be 25.12±3.46, 24.48±2.71 and 20.23±2.04 for T1, T2 and T3 groups, respectively. The present study revealed that restricted suckling improved the growth performance of Hampshire piglets and decrease the cost of feeding.